Images of social control. Fear and shock in the viewer of a world under threat - Vázquez Couto , David (Re-visiones, 2024)
Control systems and audiovisual technologies have a bilateral alliance that enables the structuring of a fear-based social discourse. If the terrible real event that unsettles the population has always been a key resource for commercial exploitation in the film industry, similarly, filmic strategies operate as an imaginary model for the recreation of the actual event. The social narrative is shaped under the constant threat of the other that induces a feeling of collective terror carefully managed by political power and mass media. Films have participated –and still do– in this process of staging of reality; however, it also warns of the danger inherent to its media status.